Modeling Syngas Fermentation for Ethanol Production under Fluctuating Inlet Gas Composition - Istiqomah, Noviani Arifina; Mukti, Rendy; Kresnowati, Made Tri Ari Penia; Setiadi, Tjandra (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Syngas fermentation effectively converts CO, H₂, and CO₂ into valuable biofuels and chemicals. This study investigated the effects of fluctuating syngas composition and kLa as the critical operational parameters on microbial fermentation performance, with a focus on ethanol, acetic acid, and biomass production. Modeling results demonstrated that increasing CO concentration significantly enhanced metabolite production, whereas increases in H₂ and CO₂ concentrations yielded limited improvements. The findings revealed that a higher H₂/CO ratio tent to reduce metabolite production, while a higher CO/CO₂ ratio significantly improved fermentation outcomes. Additionally, higher kLa values were observed to promote metabolite production, though diminishing returns were evident at very high kLa levels. Further study on the impact of syngas composition disturbances (±5% to ±20%) and fluctuation durations (0.5, 1, 2, and 4 days) indicated that larger disturbances and longer fluctuation durations led to greater deviations in metabolite concentrations, with ethanol being the most sensitive, followed by acetic acid and biomass. Despite these fluctuations, the microbial system displayed resilience, stabilizing once gas composition returned to normal levels. These insights underscored the adaptability and robustness of syngas fermentation systems, making them viable for industrial applications where gas composition variability is inevitable. The ability to tolerate moderate fluctuations offers opportunities to reduce gas pretreatment costs and process syngas from diverse sources, benefiting industries such as steel manufacturing, oil refining, and biomass gasification. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).